2016
DOI: 10.1017/s0007114516001732
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate ameliorates copper-induced oxidative injury by regulating antioxidant defences in fish intestine

Abstract: The objective of this study was to determine the protective effect of glutamate (Glu) in Cu-induced oxidative injury in fish intestine in vivo and enterocytes in vitro. The results indicated that exposure to 6 mg/l Cu for 72 h induced the production of reactive oxygen species, thereby increasing protein oxidation and lipid peroxidation in enterocytes of grass carp in vitro. Cells exposed to Cu alone resulted in a significant increase in lactate dehydrogenase release, which is accompanied by depletions of antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 60 publications
(100 reference statements)
1
12
0
1
Order By: Relevance
“…In the early stage of growth, amino acids in diets are mainly used to synthesize growth proteins. Marine fish, especially marine carnivorous fish, are very sensitive to the change in amino acid composition with the replacement of FM with plant protein (Jiang et al, 2016). The intestinal morphology growth of fish will be largely limited by the lack of amino acids, if dietary amino acid composition becomes different.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of growth, amino acids in diets are mainly used to synthesize growth proteins. Marine fish, especially marine carnivorous fish, are very sensitive to the change in amino acid composition with the replacement of FM with plant protein (Jiang et al, 2016). The intestinal morphology growth of fish will be largely limited by the lack of amino acids, if dietary amino acid composition becomes different.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that, as in mammals, the Thr could activate the PI3K/ AKT/TOR signalling pathways via IGF-I and contribute to muscle protein synthesis and growth in fish. In fish, PC and MDA contents are widely used as markers for protein oxidation and lipid peroxidation, respectively (76) . Increasing evidence indicates that the efficiency of myogenic differentiation is reduced by oxidative damage (27,77,78) .…”
Section: Antioxidant-related Parameters In Musclementioning
confidence: 99%
“…Similar results are found in the intestine of grass carp (24) . Antioxidant enzyme activities were closely related to their mRNA levels in fish (76) . The present study indicated that dietary Thr increased mRNA levels of CAT and GST in muscle, which showed the same trend to their enzyme activities.…”
Section: Antioxidant-related Parameters In Musclementioning
confidence: 99%
“…Meanwhile, from the right sides of the same sh, muscle samples were obtained determination of physiochemical-and antioxidant-related parameters. The muscle samples from the left sides of another 6 sh were frozen in liquid nitrogen, and then stored at -80 °C for biochemical parameters and molecular analysis [49]. The muscle from the right sides of same 4 sh were cut into two parts of 1×1×1 cm 3 muscle blocks using a mold, which were used for the determination of texture parameters [6].…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…The supernatant was collected for enzyme activity analysis. The contents of protein, MDA, PC, GSH and the activities of T-SOD, CAT, GPX, GST, GR, ASA, and AHR were measured using commercial kits [49]. The ROS contents were measured as decreased by LeBel et al [52].…”
Section: Sample Collection and Analysismentioning
confidence: 99%